2021
DOI: 10.1080/21655979.2021.1965696
|View full text |Cite
|
Sign up to set email alerts
|

Argon inhibits reactive oxygen species oxidative stress via the miR-21-mediated PDCD4/PTEN pathway to prevent myocardial ischemia/reperfusion injury

Abstract: The objective of this study was to explore the effect of argon preconditioning on myocardial ischemia reperfusion (MI/R) injury and its mechanism. Cardiomyocytes H2C9 were pre-treated with 50% argon, and a cell model of oxygen-glucose deprivation (OGD) was established. CCK-8 and cytotoxicity detection kits were used to detect cell viability and lactate dehydrogenase (LDH) release. The miR-21 expression was detected using quantitative real-time polymerase chain reaction. Western blot analysis was performed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
(39 reference statements)
1
14
0
1
Order By: Relevance
“…It has been established that PDCD4 is crucial in regulating oxidized low-density lipoprotein (ox-LDL) metabolism, foam cell formation, coronary atherosclerosis, stress, and ischemia/reperfusion-induced cellular injuries [10][11][12]24]. From our luciferase analysis experiment results, from the TargetScan database, and also from other studies, it was confirmed that PDCD4 is the direct target protein of miR-21 [20,24,25].…”
Section: Mediators Of Inflammationsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been established that PDCD4 is crucial in regulating oxidized low-density lipoprotein (ox-LDL) metabolism, foam cell formation, coronary atherosclerosis, stress, and ischemia/reperfusion-induced cellular injuries [10][11][12]24]. From our luciferase analysis experiment results, from the TargetScan database, and also from other studies, it was confirmed that PDCD4 is the direct target protein of miR-21 [20,24,25].…”
Section: Mediators Of Inflammationsupporting
confidence: 58%
“…It has been established that PDCD4 is crucial in regulating oxidized low-density lipoprotein (ox-LDL) metabolism, foam cell formation, coronary atherosclerosis, stress, and ischemia/reperfusion-induced cellular injuries [10][11][12]24]. From our luciferase analysis experiment results, from the TargetScan database, and also from other studies, it was confirmed that PDCD4 is the direct target protein of miR-21 [20,24,25]. The present study detected expressions of mir-21 in HR-exposed HUVECs which were highly upregulated as compared with the control group, but there were no significant effects noted between NC and HR groups.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…As AGO2 play pivotal roles in miRNA-mediated gene silencing, targeting AGO2 by 1 a and 1 b should rescue the Chemistry-A European Journal protein expressions of target mRNAs. It has been reported that miR-21 could target PTEN and PDCD4, [15] miR-25 could regulate BIM, [16] BCLÀ W and SRF were the targets of miR-122 [17] and miR-133a, [18] respectively. Then, protein expression levels of these genes were investigated after cells were treated with 10 μM 1 a and 1 b for 48 h. Compared to DMSO control, 1 a and 1 b led to significant increase in the protein levels (Figure 5), demonstrating the potential of 1 a and 1 b in regulating downstream targets of endogenous miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Zhou W et al proved that miR-21 could inhibit periodontitis by downregulating inflammation [ 52 ]. A study by Qi H et al reported miR-21 protects cardiomyocytes from ROS oxidative stress [ 53 ]. Another study by Li H et al indicated that the regulation of miR-21-5p suppresses hypoxia/reoxygenation injury-induced apoptosis of type II alveolar epithelial cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%